Similarity and co-expression of tumour-associated antigens recognised by different monoclonal antibodies. - Sakahara, H. (Nature Publishing Group, 1993)
The concentration of carcinoembryonic antigen (CEA), CA130, CA125, SLX, CA19-9, SPan1, and tumour-associated glycoprotein 72 (TAG-72) in the culture supernatant of 15 cancer cell lines and in the sera of 58 cancer patients was measured, and the co-expression of these antigens was examined by double determinant immunoradiometric assays. The high correlation coefficient of the concentrations and significant binding in the double determinant assays indicated a close relationship between CA125 and CA130 and between CA19-9 and SPan1. There was variable binding of the 125I-labelled anti-SLX, anti-CA19-9, and anti-SPan1 antibodies to anti-CA130 beads that had been pre-incubated with the culture supernatants, suggesting the presence of the epitopes of SLX, CA19-9, and SPan1 on the molecule expressing CA130. Similarly, the epitopes of SLX, CA19-9, and SPan1 could be present on the molecule expressing CEA. 125I-labelled anti-CA19-9, anti-SLX, and anti-TAG-72 antibodies were bound in variable proportions to anti-CA130 beads or to anti-CEA beads that had been pre-incubated with patients' sera. However, CEA and CA130 were not expressed on the same molecule, either in the culture supernatant, or in patients' sera. In conclusion, the carbohydrate epitopes of CA19-9, SPan1, SLX, and TAG-72 could be present on the molecule recognised by the anti-CA130 or anti-CEA antibody; however, the epitopes of CA130 and CEA did not co-exist on the same molecule.